2011
DOI: 10.1007/s10640-011-9520-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Formal and Informal Regulations on Environmental and Economic Performance of Brazilian Manufacturing Firms

Abstract: This study investigates the impact of formal and informal regulations on environmental and economic performance of Brazilian manufacturing firms. We adopt a dual approach where production technology is represented by a cost function, approximated by a translog form. Pollution is considered as a negative by-product that can be modified trough using either formal regulation (inspections or sanctions) or informal regulation (community pressure). A simultaneous equation model is estimated by three-stage least squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 24 publications
2
78
0
1
Order By: Relevance
“…Furthermore, Ma et al (2012) also supported the empirical findings [31]. Féres J. et al (2012) found that regulatory environmental regulation would inhibit technology innovation, while the governmental financial and policy support for enterprise innovation would increase the burden on enterprises [32]. Rooij et al (2013) pointed out that excessive government support inhibits social support, thereby reducing the potential for innovative benefits from voluntary environmental regulation [33].…”
Section: Environmental Regulation Government Randd Funding and Green Tmentioning
confidence: 54%
“…Furthermore, Ma et al (2012) also supported the empirical findings [31]. Féres J. et al (2012) found that regulatory environmental regulation would inhibit technology innovation, while the governmental financial and policy support for enterprise innovation would increase the burden on enterprises [32]. Rooij et al (2013) pointed out that excessive government support inhibits social support, thereby reducing the potential for innovative benefits from voluntary environmental regulation [33].…”
Section: Environmental Regulation Government Randd Funding and Green Tmentioning
confidence: 54%
“…Meanwhile, the weak formal regulation in developing countries exerts an important influence on firms, which adopt voluntary environmental strategies [9]. Thus, external stakeholders, such as professional and trade associations, academic institutions, supranational and national entities and industry initiatives [55], exert normative pressures in order to promote environmental values and norms of conduct that firms may voluntarily adopt, encouraged by non-coercive mechanisms such as public attention, peer industry pressures and the embarrassment of noncompliance [73].…”
Section: Hypothesis 1 (H1) Corporate Environmental Performance (Cep)mentioning
confidence: 99%
“…The minimization of the environmental damages caused by business activity and the protection of the natural environment are signals of firms' environmental performance, and have received increasing attention from society, which require firms to reduce their negative impact on environment, contributing to sustainable development [9]. Thereby, firms are expected to decrease and control the consumption of natural resources and energy, and to reduce or eliminate the production of waste and pollutants during and after the production process; firms can also develop new environmentally friendly products that minimize their ecological footprint [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulative pressures include both formal and informal pressures. Formal regulative pressures are exerted by authorities for regulating pollution emissions (Féres & Reynaud, : p3), which gain compliance by enacting laws, policies, and rules and create deterrence through punishment (Li & Ding, ; Liu, Ke, Wei, Gu, & Chen, ). Organizations are forced to assure compliance with the formal regulative pressures (Hoffman, ) and control their behaviors to obtain legitimacy (Lounsbury & Glynn, ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%